2019
DOI: 10.1080/14789450.2019.1592681
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic profiling of urine: implications for lupus nephritis

Abstract: Introduction: Lupus nephritis (LN) is a common and significant manifestation, affecting 60% of adults and 80% of children with systemic lupus erythematosus, with up to 30% of patients progressing to end stage renal disease. There remains an unmet need for non-invasive markers of disease activity, damage, and response to therapy. In addition, non-invasive biomarkers that predict therapeutic efficacy are needed to enable cost-effective clinical trials of novel agents. Areas covered: This review examines the meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 86 publications
(94 reference statements)
0
16
0
Order By: Relevance
“…Cellular features not captured by scRNA-seq-These scRNA-seq approaches do not provide direct measurements of microRNA, proteomic or metabolic data, although some insights can be inferred. Although such analyses have been performed on blood and urine of patients with SLE [92][93][94] , none have been performed on tissue. Technical advances that combine cell surface protein detection with scRNA-seq, such as REAP-seq and CITE-seq 95, 96 , enable the correlation of protein expression with transcriptomic data and are of great interest in the analysis of tissue pathology.…”
Section: Limitations Of Scrna-seq and Next Stepsmentioning
confidence: 99%
“…Cellular features not captured by scRNA-seq-These scRNA-seq approaches do not provide direct measurements of microRNA, proteomic or metabolic data, although some insights can be inferred. Although such analyses have been performed on blood and urine of patients with SLE [92][93][94] , none have been performed on tissue. Technical advances that combine cell surface protein detection with scRNA-seq, such as REAP-seq and CITE-seq 95, 96 , enable the correlation of protein expression with transcriptomic data and are of great interest in the analysis of tissue pathology.…”
Section: Limitations Of Scrna-seq and Next Stepsmentioning
confidence: 99%
“…In recent years, with the wide use of immunosuppressants and biological agents, the prognosis and survival rate of patients with LN have improved; however, 10–20% of the patients with LN progress to ESRD, which is linked to a heavy burden and morbidity ( Aljaberi et al, 2019 ). So, there is a need to study the pathophysiology and discover new therapeutic methods to prevent LN progression and prolong patient survival.…”
Section: Discussionmentioning
confidence: 99%
“…Lupus nephritis (LN) is one of the most common and severe complications of systemic lupus erythematosus (SLE) and seriously affects the quality of life and prognosis of SLE patients. About 80% of children and 60% of adults are susceptible, and up to 30% of patients could progress to end-stage renal disease (ESRD) [ 1 ]. Previous studies investigated 491 cases of LN patients in central plains of China with 5-year, 10-year, 15-year, and 20-year survival rates of 88%, 77%, 53%, and 46%, respectively, and found that renal failure was the main cause of death [ 2 ].…”
Section: Introductionmentioning
confidence: 99%